The Influence of Work Passion, Employee Engagement, and Performance Appraisal on Turnover Intention: The Mediating Role of Job Satisfaction at Shieraki Group - Mombang Sihite; Seta A Wicaksana; Sri Nadiroh (ESENSI: Jurnal Manajemen Bisnis, 2026)
The fashion industry is among the retail and consumer products sectors with the highest employee turnover rates, as reported by a LinkedIn survey in 2024. This study was conducted at a fashion brand company called Shieraki Group, aiming to examine the influence of Work Passion, Employee Engagement, and Performance Appraisal on Turnover Intention, with Job Satisfaction as a mediating variable among Shieraki Group employees. Data were collected through questionnaires distributed to all 35 employees using a five-point Likert scale, with a saturated sampling technique. Data analysis included descriptive statistics, validity and reliability tests, and hypothesis testing using a bootstrapping method with 5,000 bootstrap samples and a 95% Confidence Interval through the Jamovi application. The results show that Work Passion has a significant negative effect on Turnover Intention, and Employee Engagement has a significant negative effect on Turnover Intention. Performance Appraisal has no significant effect on Turnover Intention. Job Satisfaction is unable to mediate the effects of Work Passion, Employee Engagement, or Performance Appraisal on Turnover Intention, as the psychological attachment of employees to their work operates directly and independently without requiring Job Satisfaction as an intermediary.